A novel design of spacecraft combined attitude & sun tracking system using a versatile fuzzy controller - Yew, Chung Chak; Varatharajoo, Renuganth (Emerald Group Publishing, 2015)
Purpose – The purpose of this paper is to develop a theoretical design for the alternative attitude control of the rotation about the pitch axis for the nadir-pointing spacecraft in the event of inertial actuator faults.